Integrating Ethiopian Indigenous Astronomical Knowledge with Modern Astrophysics: A Framework for Cultural Preservation and Scientific Discovery - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2025)
Ethiopia’s rich ethnoastronomical heritage, particularly the Borana Oromo lunar-stellar calendar and similar systems among Amhara, Tigray, Afar, Somali, Konso, and other groups, integrates celestial observation with seasonal forecasting, pastoral mobility, ritual timing, and social organization (Gadaa cycles). These knowledge systems face accelerating threats from elder attrition, urbanization, modernization, and climate variability. Purpose: This study maps the contemporary distribution, linguistic and narrative structure, scientific validity, educational integration potential, and citizen-science documentation pathways of Ethiopian Indigenous Astronomical Knowledge (EIAK), aiming to provide evidence-based strategies for preservation and application. A mixed-methods design combined quantitative visualization (distribution maps, correlation matrices, time-series validation against modern meteorological records), qualitative semantic and narrative analysis, competency assessment in educational pilots, and participatory citizen-science metrics. Novelty: The work offers the first comprehensive synthesis integrating multi-ethnic holder distributions, narrative keyword networks, rigorous predictive validation (r = 0.889 for rain onset, RMSE = 3.3 days), culturally responsive STEM curriculum frameworks, and scalable citizen-science models for an African indigenous astronomy system. Findings: Knowledge is concentrated in Oromia, SNNPR, and Amhara; oral transmission dominates (64.3%); narratives emphasize time, weather, and navigation; predictive skill is high for rain onset and seasonal transitions; low-cost educational models (Community Elder, Cultural Exchange) achieve highest adoption and competency gains; citizen-science programs engaged >18,000 participants with strong sustainability in community-led formats. EIAK is a scientifically valid, adaptive knowledge system with proven forecasting utility and significant educational value, yet urgently requires safeguarding. Recommendations: Prioritize multi-ethnic documentation, large-scale validation, equitable educational scaling, sustainable citizen science, and policy integration.